Pengaruh Karakteristik Perusahaan dan Corporate Social Responsibility Terhadap Agresivitas Pajak: Studi Kasus pada Perusahaan Industri Subsektor Kimia yang Terdaftar di BEI Tahun 2020-2024 - Lesi; Iwin Arnova; Nina Yulianasari (Economic Reviews Journal, 2025)
This study aims to determine the effect of company characteristics and corporate social responsibility on tax aggressiveness (Case study of chemical subsector industrial companies listed on the IDX in 2020-2024) The type of data used in the study is quantitative data. The sample in this study was 8 chemical companies listed on the IDX in 2020-2024. The analysis method used is multiple linear regression analysis and hypothesis testing.). The results of the study show that Profitability has a negative effect on tax aggressiveness because the regression direction shows a value of -0.492 with a significance value of 0.871> 0.05. This means that the higher the profitability (the company's ability to generate profits), the lower the tax aggressiveness of chemical companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Company size) has a negative effect on because the regression value is -8.661 with a significance value of 0.041 <0.05. This means that the larger the size of a company, the lower the level of tax aggressiveness of chemical companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Corporate social responsibility) has a positive effect on tax aggressiveness (Y) because the regression value is 7.541 with a significance value of 0.000 <0.05. Since the significance value is less than 0.05, it means that Corporate social responsibility has an effect on Tax Aggressiveness in Chemical Companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. Simultaneous hypothesis testing shows a significance value of 0.004 <0.05. This means that together Profitability, company size) and corporate social responsibility have a significant effect on Tax Aggressiveness.